MANAGEMENT SYSTEMS HUMANIZATION AND GROWTH OF CREATIVE POTENTIAL IN RUSSIA - V. Zavolokin (Вестник Северо-Кавказского федерального университета, 2022)
In article the author considers a problem of a humanization of management systems in Russia for ensuring growth of creative potential ofpeople who are involved in the organized relations. The complex humanization is necessary. Creative potential of the person, his energy and vigor bear in themselves direct consequences and manifestations of influence of the versatile management systems and social and economic determinants established by administrative and economic actions of a near and far environment. Of set of social and economic and other factors there is a palette of actions and the relations which eventually causes efficiency, stability and quality of creative manifestations of the person and community, results and products of human work.